THE EFFECTIVENESS OF SEND A PROBLEM TECHNIQUE FOR TEACHING WRITING AN ANALYTICAL EXPOSITION TEXT (A Quasi-Experimental Study of the Eleventh Grade Students of SMA N 8 Semarang in the Academic Year 2015/2016) (ELT Forum: Journal of English Language Teaching, 2016)
The aim of the study is to find out whether teaching writing analytical exposition text by using Send a Problem technique is effective or not for Senior High School students. In the working hypothesis (H1), â€œThere is significant difference in studentsâ€™ writing achievement between those who are taught using Send a Problem and those who are taught using conventional way.â€ Meanwhile, in the null hypothesis (Ho), â€œThere is no significant difference in the studentsâ€™ writing achievement between those who are taught using Send a Problem and those who are taught using conventional way.â€The population of this study was the eleventh grade students of SMA Negeri 8 Semarang in the academic year 2015/2016. The total number of the sample was 60 students that consisted of 30 students of class XI IS 4 as the experiment group who were taught using Send a Problem technique and 30 students of class XI IS 5 as the control group who were taught using conventional way. The design of this study was a quasi-experimental study. The data were collected through the writing test. In the pre-test, the mean score of the experimental group was 62.80 and the control group was 62.77. After the treatment, the result of post-test of the experimental group was 75.57 while the control group was 68.57. The independent sample t-test used by the writer showed that there was a significant difference between post-test of control group and experimental group. Lastly, teaching writing analytical exposition text using Send a Problem technique is effective than conventional way. English teachers are suggested to concern better in their technique variety in teaching writing any kind of texts especially analytical exposition text.